Effects of Anti-NGF on Apoptosis in Rats with Experimentally Induced Sepsis Model - Bayar, Mustafa; Ozer, Belin; Bestas, Azize; Ceribasi, Songul; Ozercan, Ibrahim (Ortadogu Ad Pres & Publ Co, 2010)
Objective: This study aimed to investigate the effects of anti-NGF administration on apoptosis in rats with experimentally induced sepsis model, and to examine the possible role of nerve growth factor (NGF) in pathogenesis and treatment of sepsis. Material and Methods: Thirty three Wistar Albino rats were randomly allocated into four groups. After sparing the control group, the remaining three groups were given intraperitoneal E. coli lipopolysaccaride to induce sepsis. Early anti-NGF group (Group EA-NGF, n=9) was injected with intraperitoneal anti-NGF one hour before LPS injection, and late anti-NGF group (Group LA-NGF, n=9) after sepsis was induced. Baselines, 2, 12, 24, and 72nd hours were analyzed to determine NGF levels. The rats were sacrificed on the 3rd day, and tissue samples separated from the small intestines, liver and lung. HE, bcl-2 and bax staining were used to evaluate apoptosis. Results: Apoptosis increased most markedly in the intestine tissue, as well as in the liver and lung tissue, and this increase was most evident in the early anti-NGF group. Bcl-2 staining in the subjects was less apparent while bax staining was more intensely detected in the sepsis groups, with a significant difference between the sepsis and early anti-NGF groups. Bax staining in the EA-NGF group was more clearly observed than that in LA-NGF group. NGF levels were found to increase in the 24th hour in sepsis group (Group S) and decrease in the second hour in Group EA-NGF. Conclusion: It can be concluded that anti-NGF administration in the early period of sepsis increases apoptosis at least to the same extent with sepsis, and it decreases apoptosis when administered in the later period of sepsis.
Deneysel sepsis modeli oluşturulan ratlarda anti-NGF uygulamasinin apopitoz Üzerindeki etkileri
Keywords: Sepsis; 7S nerve growth factor protein, mouse; apoptosis